The role of waqf properties in the development of the Islamic institutions in the Philippines: Issues and challenges. - Gamon, Alizaman Dumangcag; Tagaranao, Mariam Saidona; Ali, Mohammed Farid (International Islamic University Malaysia, 2018)
Waqf system continued to be the most successful ways by which endowments or revenues of assets can be dedicated by benefactors, purposely for the welfare of the Muslim Ummah. It is highly revered when waqf funds have been used in building mosques, madrasah, orphanage centers, colleges and universities as well as providing free medical services for the needy Muslims. Waqf is considered as an indispensable institution, which can offer Islamic financial facilities for the socio-economic development of the Bangsamoro. This research discusses the role of waqf properties in the development of the Islamic institutions in the Philippines. It also analyses and evaluates the issues and challenges faced by the Muslim minorities in the management and development of waqf properties in a country dominated by Catholic Christians. For sustainable development, this research recommends the establishment of a credible waqf-based model in management and financing which will provide a strong support in the establishment of health clinic, Islamic religious centers and educational institutions. This paper concludes that unity among the scholars (‘ulamas) and Muslim non-governmental organizations through implementation of a uniform waqf management can strengthen the role of awqaf properties in developing the Islamic institutions in the Philippines.